2000
DOI: 10.1111/j.1528-1157.2000.tb04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin Versus Vigabatrin as First Add‐On for Patients with Partial Seizures That Failed to Respond to Monotherapy: A Randomized, Double‐Blind, Dose Titration Study

Abstract: Approximately one third of the patients in both groups became seizure-free. Although no major differences were seen in terms of the improvement rate between the groups, equivalence between the two drugs was not found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 13 publications
(9 reference statements)
0
34
0
1
Order By: Relevance
“…131 The remaining study was discontinued prematurely and failed to recruit the required number of participants. 132 This study also found baseline differences between treatment groups in the duration of epilepsy and in some cases doses of GBP and VGB exceeded the recommended limit.…”
Section: Newer Drugs Versus Newer Drugs a Seizure Frequency I Seizumentioning
confidence: 67%
See 4 more Smart Citations
“…131 The remaining study was discontinued prematurely and failed to recruit the required number of participants. 132 This study also found baseline differences between treatment groups in the duration of epilepsy and in some cases doses of GBP and VGB exceeded the recommended limit.…”
Section: Newer Drugs Versus Newer Drugs a Seizure Frequency I Seizumentioning
confidence: 67%
“…61,131,132 Two studies used treatment periods of 24 weeks 131,132 and the third followed treatment over a period of 18 months. 61 Two trials included patients with partial seizures 61,132 and the third included patients with partial or generalised seizures. 131 Two trials compared GBP with LTG 61,131 and two compared GBP with VGB.…”
Section: Newer Drugs Versus Newer Drugs a Seizure Frequency I Seizumentioning
confidence: 99%
See 3 more Smart Citations